Ileal fecalomas causing small bowel obstruction: A case report. (August 2021) - Tiruneh, Abraham Genetu; Merine, Seyoum Kassa; Solomon, Mesale
Abstract: Introduction: Fecaloma is an accumulation of feces that has formed a mass and has failed to be expelled spontaneously. Because fecal matter is harder and firmer in the left side of colon, and the diameter of the bowel is smaller compared to the right, fecalomas mostly form in recto-sigmoid area. Small bowel fecaloma formation is an extremely rare condition. Case presentation: We report a 49 years old man who presented with small bowel obstruction due to ileal fecalomas for whom enterotomy and removal of fecaloma was done with good outcome. Discussion: Fecal matter can accumulate in the intestinal lumen to form a mass separate from other intestinal contents which eventually becomes fecaloma. Formation is usually related to chronic constipation, conditions causing intestinal motility disorder, or in psychiatric patients who could have ingested extraordinary substances. Fecaloma can present as abdominal mass, stercoral colitis, urinary retention or intestinal obstruction. Treatment options include conservative management with bowel rest, laxatives, endoscopic removal, laparotomy and removal via enterotomy. Conclusion: Fecaloma can be considered in patients who present with small bowel obstruction without any risk factors. Initial noninvasive management should be considered. Failed conservative treatment can be followed by laparotomy and fecaloma removal. Highlights: Fecaloma is an accumulation of feces that has formed a mass and has failed to be expelled spontaneously. Most patients have risk factors in form of intestinal motility disorder, constipation or psychiatric disorder. Small bowel fecaloma is extremely rare without such risk factors. Spontaneous formation of fecaloma in small bowel can present with intestinal obstruction.